Synthesis of epoxidized natural rubber grafted with hyaluronic acid for the development of biomaterials - Quevedo, Bruna V.; Komatsu, Daniel; de Lourdes Rezende, Maira; de Rezende Duek, Eliana Aparecida (International journal of biological macromolecules, 2023)
Natural Rubber (NR), extracted from Hevea brasiliensis rubber trees, is a biocompatible biopolymer with properties that support in the tissue repair process. However, its biomedical applications are limited due to the presence of allergenic proteins, hydrophobicity, and unsaturated bonds. To overcome these limitations and contribute to the development of new biomaterials, this study aims to deproteinize, epoxidize, and subject NR to copolymerization by grafting with hyaluronic acid (HA), which is widely recognized for its bioactive properties in the medical field. The deproteinization, epoxidation, and graft copolymerization through the esterification reaction were confirmed by Fourier Transform Infrared Spectroscopy and Hydrogen Nuclear Magnetic Resonance Spectroscopy analysis. Thermogravimetry and Differential Scanning Calorimetry demonstrated that the grafted sample exhibited a lower degradation rate and a higher glass transition temperature, indicating strong intermolecular interactions. Moreover, contact angle measurement revealed that the grafted NR exhibited a high hydrophilic character. The results obtained suggest the formation of a novel material with great potential for application in biomaterials involved in tissue repair processes. •Natural rubber deproteinization•Natural rubber in situ epoxidation•Modification of epoxidized natural rubber via grafting with hyaluronic acid•Esterification reaction